Supervision of Education Quality at Sonder State Junior High School, North Sulawesi, Indonesia - Lumi, Eirene Hana; Sumual, Shelty DM; Krowin, Martinus M. (Researchparks Publishing, 2023)
The place or location of this research is SMP Negeri 1 Sonder which is located on Jalan Tounelet Village, Sonder District, Minahasa Regency, North Sulawesi Province. Based on the characteristics of the problems studied and the research sites chosen, the implementation of this research will take place from November 2021 – February 2022. This research is a research that uses a descriptive method with a qualitative approach. The descriptive method is the method of exposing findings based on facts yAfter doing research with the Implementation of Educational Quality Supervision at SMP Negeri 1 Sonder, contained in the previous chapters, it can be concluded that on The leadership of the principal at SMP Negeri 1 Sonder generally has Good. Where is the evaluation SMP Negeri 1 Sonder with the following results: Carry out supervision of teachers withprovide assistance and facilities for teaching materials necessary, he providing facilities such as providing book references for teachers who need them as well as directing teachers to choose appropriate teaching materials. The success of a school is certainly centered on the principal and controls well on the development of teachers, staff, administration, and staff within the scope of the organization or school phenomena obtained based on data collected from the field.